(untitled) (Annals of Medical Research, 2022)
Aim: To evaluate the nutritional status of hospitalized patients and the consumption of foods offered in the hospital and to assess the factors affecting their food consumption. Materials and Methods: Patients over 18, who were hospitalized in the internal medicine clinics for at least 72 hours and could take oral food, were included in the study. Patients’ anthropometric measurements, demographic characteristics, and current diseases were recorded, and NRS 2002 scores were calculated. The primary endpoint was to determine the patients’ food consumption in the hospital and the reasons for insufficient consumption. The secondary endpoint was the comparison of the results according to the NRS score. Results: A total of 200 patients participated in the study. The mean age was 66±18 years. NRS≥3 was in 48% of patients (n=96) and the body mass index of these patients was lower than patients with NRS<3 (27±5 vs. 25±5; P= 0.002). They were older (60±18 vs. 73±14; p= 0.005), and their duration of hospitalization was longer (5±3 vs. 7±7; p= 0.03). In the group with NRS≥3, the rate of receiving nutritional support was 38.5%. In the whole group, the rate of consuming less than half of the hospital food was 75% and 86.5% in those with nutritional risk. When the factors affecting the preference of hospital meals were questioned, answers varied, such as not serving the food at the appropriate temperature, sour taste of the food, inconsistency of the foods on the menu in terms of taste and content. Only 4% of patients stated that they would prefer hospital menus as their diet menu at home. Conclusion: Half of the patients hospitalized in the internal medicine clinic are at risk of malnutrition. Nutritional support is also insufficient. To reduce inadequate food consumption during hospitalization, the causes should be analyzed, and measures should be taken.